2020
DOI: 10.3389/fneur.2020.01022
|View full text |Cite
|
Sign up to set email alerts
|

Blood Neutrophil/Lymphocyte Ratio Is Associated With Cerebral Large-Artery Atherosclerosis but Not With Cerebral Small-Vessel Disease

Abstract: Background and Objective: The blood neutrophil/lymphocyte ratio (NLR) is a marker of peripheral inflammation, with a high NLR associated with an increased risk of cardiovascular events and poor prognosis in ischemic stroke. However, few data are available on the differential impact of the blood NLR on different silent cerebral vascular pathologies, including cerebral large-artery atherosclerosis (LAA) and cerebral small-vessel disease (CSVD), in neurologically healthy individuals. Methods: We evaluated cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 48 publications
2
9
1
Order By: Relevance
“…Neutrophil-to-lymphocyte ratio, a biomarker indicating systemic inflammatory status, has been shown to be related to intracranial atherosclerosis. A study by Chung et al (29) revealed that high NLR was correlated with intracranial atherosclerosis (OR= 1.87; 95% CI, 1.15-3.06; P = 0.01) in healthy individuals, consistent with another study by Nam et al (15) indicating that NLR could be a predictor for the prevalence and burdens of ICAS. However, few studies revealed the independent predictive values of NLR in the prognosis of sICAS.…”
Section: Discussionsupporting
confidence: 76%
“…Neutrophil-to-lymphocyte ratio, a biomarker indicating systemic inflammatory status, has been shown to be related to intracranial atherosclerosis. A study by Chung et al (29) revealed that high NLR was correlated with intracranial atherosclerosis (OR= 1.87; 95% CI, 1.15-3.06; P = 0.01) in healthy individuals, consistent with another study by Nam et al (15) indicating that NLR could be a predictor for the prevalence and burdens of ICAS. However, few studies revealed the independent predictive values of NLR in the prognosis of sICAS.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, Ying et al concluded that elevated admission NLR level was an independent factor associated with stroke severity and prognosis in symptomatic intracranial atherosclerosis patients ( 6 ). The relationship between extracranial large-artery stenosis and elevated NLR level was also reported by Chung et al in line with our results ( 35 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding of high NLR level in intracranial stenosis is in accordance with previous studies. Chung et al have revealed that high NLR was correlated with intracranial large-artery atherosclerosis in individuals without neurological diseases ( 35 ). Nam et al also reported that NLR was associated with both prevalence and burdens of intracranial atherosclerosis in a healthy population ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Leukocytosis, including monocytosis, is a known risk factor for atherogenesis that can contribute to the imbalance of lesional leukocytes. 26 Upon WTD feeding, the ratio of blood neutrophils to lymphocytes was increased, suggesting WTD-induced systemic inflammation 27,28 that was not impacted by mouse genotype, sex, or models. Despite the difference in plasma cholesterol levels, cholesterol contents of resident peritoneal macrophages from male and female mice were similar between genotypes (Figure S6).…”
Section: Ilrun Deficiency Promotes In Situ Efferocytosis and Reduces ...mentioning
confidence: 99%